Development of Thematic Learning Using the Field-Trip Method Assisted by the Surrounding Environment to Improve Students' Scientific Literacy Abilities - Sri Luah; Parmin Parmin; Widiasih Widiasih (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study is to produce learning tools with a field-trip learning method assisted by the surrounding environment to improve students' scientific literacy skills. The learning tool developed in this class VI material has the theme of saving living things with the subtheme of plants, friends. Development device learning refers to the Borg & Gall model which consists of 7 steps. Thematic learning tools with the field-trip method assisted by the surrounding environment were validated by 3 expert validators in the fields of science, language and instructional design learning so that results that met the following valid success criteria were obtained: Syllabus 4.48 (very good category), RPP 3.95 (good category), student teaching materials 3.81 (good category), and LKS 4.35 (very good category). The results of the effectiveness test of the learning tool were carried out on grade VI students of SDN Dampyak 02, resulting in an increase in scientific literacy skills of 4.14 (good category). Effectiveness was also obtained when teachers managed learning by 4.56 (very good category). The level of practicality of the field trip method during learning was 4.14 (good category), 4.30 (very good category). Thus, the overall learning tools of the field trip method developed are valid, effective, and practical.